Pengaruh Kompetensi Sumber Daya Manusia dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Keuangan Daerah Dengan Komitmen Organisasi Sebagai Variabel Moderating - Alim Azhari Muttaqien; Jamaluddin Majid; Nur Rahma Sari (Indonesian Journal of Taxation and Accounting, 2024)
This study aims to determine the effect of human resource competence and internal control systems on the accountability of regional financial management with organizational commitment as a moderating variable (Studies in the Regional Government of Tana Toraja Regency). This research is a quantitative research. This research was conducted at the Regional Work Unit (SKPD) of Tana Toraja Regency, to be precise, in 16 offices and 4 agencies. The subjects in this study were heads of offices or agencies, treasurers, and heads of departments. The sample collection technique in this study used a simple random sampling method. The data collection method was carried out using a questionnaire using a Likert scale. The data analysis technique used is descriptive statistics, data quality test, classic assumption test and hypothesis testing with the help of a computer through the IBM SPSS 21 for windows program. The results of this study are (1) Human Resource Competence has a positive and significant effect on Regional Financial Management Accountability, (2) Internal Control Systems have a positive and significant effect on Regional Financial Accountability, (3) Organizational Commitment is able to moderate the relationship of Human Resource Competence on Management Accountability Regional Finance, (4) Organizational Commitment is able to moderate the relationship between the Internal Control System and the Accountability of Regional Financial Management organizational performance.